2020
DOI: 10.4322/2526-8910.ctoao1974
|View full text |Cite
|
Sign up to set email alerts
|

Situación ocupacional y recursos sociales de las mujeres mayores en situación de dependencia atendidas por un servicio de ayuda a domicilio en el ámbito rural

Abstract: Este es un artículo publicado en acceso abierto (Open Access) bajo la licencia Creative Commons Attribution, que permite su uso, distribución y reproducción en cualquier medio, sin restricciones siempre que el trabajo original sea debidamente citado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
2
Order By: Relevance
“…As populações residentes do meio rural, por sua vez, podem sofrer um processo de ruptura em sua vida cotidiana, seja por acidentes, pela marginalização social ou pelo isolamento (Crouch, 2008;Kingston et al, 2010;Parsons & Stanley, 2008;Prieto-Bueno & Cantero-Garlito, 2020). Nesse sentido, o processo de adaptação parece requerer uma reorganização dos fazeres e das ocupações da vida diária (Kingston et al, 2010;Parsons & Stanley, 2008).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As populações residentes do meio rural, por sua vez, podem sofrer um processo de ruptura em sua vida cotidiana, seja por acidentes, pela marginalização social ou pelo isolamento (Crouch, 2008;Kingston et al, 2010;Parsons & Stanley, 2008;Prieto-Bueno & Cantero-Garlito, 2020). Nesse sentido, o processo de adaptação parece requerer uma reorganização dos fazeres e das ocupações da vida diária (Kingston et al, 2010;Parsons & Stanley, 2008).…”
Section: Discussionunclassified
“…A desigualdade social também é algo que perpassa o cotidiano de muitas pessoas no mundo rural. A pobreza, a vulnerabilidade social e a exploração da mão de obra são fatores estressores que afetam a participação social de pessoas de diversas idades (Bartie et al, 2016;Crouch, 2008;Prieto-Bueno & Cantero-Garlito, 2020;Santos & Menta, 2016). No entanto, atividades físicas e de relaxamento podem servir como estratégias promotoras de saúde e qualidade de vida (Crouch, 2008).…”
Section: Discussionunclassified
“…Populations residing in rural areas, in turn, may suffer a process of rupture in their daily lives, whether due to accidents, social marginalization or isolation (Crouch, 2008;Kingston et al, 2010;Parsons & Stanley, 2008;Prieto-Bueno & Cantero-Garlito, 2020). In this sense, the adaptation process seems to require a reorganization of tasks and occupations of daily life (Kingston et al, 2010;Parsons & Stanley, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Social inequality is also something that permeates the daily lives of many people in the rural world. Poverty, social vulnerability and labor exploitation are stressors that affect the social participation of people of different ages (Bartie et al, 2016;Crouch, 2008;Prieto-Bueno & Cantero-Garlito, 2020;Santos & Menta, 2016). However, physical and relaxation activities can serve as strategies to promote health and quality of life (Crouch, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition to health impairment-related constraints, leisure opportunities may also be impacted by other variables, such as the environment in which the individual lives, particularly in the case of dependent people in rural areas. 28 Participation in leisure activities has been found to be effective in improving depressed mood and increasing psychological well-being, 16 and it has also been shown that general life satisfaction is related to life outlook and health status, which in turn determine participation in activities. 29 However, the relationship between leisure and health may be even more complex since gender may act as a moderating factor between different health-related variables.…”
Section: Leisure and A Positive Leisure Attitudementioning
confidence: 99%